The perceptions of the teaching staff regarding selection for the Bachelor of Social work (BSW) program at the University of Cape Town (UCT) - Khan, Latifa (Department of Social Development, 2021)
The Apartheid system had a tremendous effect on education in South Africa. Education occurred in segregated environments, controlled by the government. The racial differentiation in universities was a clear indication of what was occurring within the society. Post-Apartheid many reforms have been made towards ensuring equal access and redress of the past inequalities especially in education. With the huge responsibility being placed on social workers in working with vulnerable populations. The aim of social work education is to promote critical responsive practice and to train students to ensure effective service delivery. This study explores the perceptions of the teaching staff regarding selection for the Bachelor of Social work (BSW) program at the University of Cape Town (UCT). The study investigated the perceptions of the teaching staff regarding the current selection process at the University of Cape Town, the benefits of implementing a Bachelor of Social Work specific selection process, the possible challenges that could be encountered and the recommendations thereof. The study adopted a qualitative research approach where data was collected using a semi structured interview schedule. The population interviewed was the University of Cape Town Department of Social Development teaching staff. The findings of the study show that there is limited knowledge of the current selection process among the teaching staff as the university uses a generalised selection process managed by administrative staff. The results of the study reveal that implementing a specific selection process could promote a higher standard of practice and may improve the reputation of the social work profession. The findings further indicated that there could be variations between the department and the university requirements if the department was mandated to manage selection of its students therefore initiating conversations around selection could be valuable. Lastly the study recommends the need for a selection process that reflected not only on the academic ability but also the personal qualities of an applicant through submission of personal statements and motivational letters, and conducting oral and demonstration interviews.